Exact Solutions of ϕ4 Equation Using Lie Symmetry Approach along with the Simplest Equation and Exp-Function Methods. (17th December 2012) - Jafari, Hossein; Kadkhoda, Nematollah; Khalique, Chaudry Masood
Abstract : This paper obtains the exact solutions of the ϕ 4 equation. The Lie symmetry approach along with the simplest equation method and the Exp-function method are used to obtain these solutions. As a simplest equation we have used the equation of Riccati in the simplest equation method. Exact solutions obtained are travelling wave solutions.